Meeting report: managing peristomal skin complications. (14th March 2019) - Bibi, Fatima
Abstract : A group of experts in stoma care attended a round-table discussion to identify prevention and management techniques on peristomal skin issues.Fatima Bibi, Project Manager at MA Healthcare, reports